Water-based anticorrosive paint and preparation method thereof
By using additives such as modified Kanaba wax microneedles and modified nanoparticles in water-based anticorrosion coatings, the problem that matte coatings in the prior art is difficult to maintain waterproofness and matte effects at the same time, achieving the improvement of high waterproofness, matte effects and anticorrosion performance, and having self-cleaning effects.
Patent Information
- Application Number
- CN202510087956.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
When existing matte paints are used in exterior walls, it is difficult to maintain high waterproofness and matte effects at the same time, resulting in insufficient anti-corrosion performance.
By preparing modified Kanaba wax microneedles and combining modified TiO2 nanoparticles, modified SiO2 nanoparticles and modified COF-5-loaded kauriene in aqueous anticorrosion coatings, the surface roughness and dispersion of the coating are improved to achieve superhydrophobicity and high matte effects.
It achieves the high waterproofness and matte effect of the paint, while improving corrosion resistance and self-cleaning effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating preparation, and in particular to a water-based anti-corrosion coating and a preparation method thereof. Background Art
[0002] As people pursue both beauty and practicality in home decoration, matte paint has gradually gained popularity due to its unique texture and visual effects. Compared with glossy paint, matte paint has environmentally friendly raw materials, good wear resistance, good scratch resistance, and especially low gloss, which can reduce the stimulation of light reflection to the eyes. Its paint surface is softer, giving people an elegant, simple, subtle and soft color experience. Therefore, this kind of paint is not only widely used in interior decoration, such as interior wall paint and furniture paint, but also has important applications in the fields of exterior wall painting.
[0003] The patent with the publication number CN113969088A and the name of a matte anti-fouling exterior waterproof coating and its preparation method and use method discloses that the raw material composition of the matte anti-fouling exterior waterproof coating includes: 500-900 parts by weight of pure acrylic emulsion, 10-40 parts by weight of matting agent, 10-100 parts by weight of hydrophobic agent, and 100-500 parts by weight of water; the matting agent is a polyethylene wax emulsion grafted with methyl methacrylate monomer; the hydrophobic agent is a fluorinated polysiloxane. The matting effect in the above technical solution is determined by the polyethylene wax emulsion grafted with methyl methacrylate monomer, which can effectively increase the roughness of the film-forming surface and effectively improve the matting performance.
[0004] However, when matte paint is applied to the exterior walls of buildings, it is necessary to cope with various weather conditions, especially in southern my country, where there are more rainy days, so there are certain requirements for the anti-corrosion properties of matte paint. The waterproof effect in the above technical solution depends on the sealing and hydrophobicity of its coating, which means that the coating surface needs as few pores as possible. However, the principle of producing the matte effect is the diffuse reflection of incident light by the tiny rough structure on the surface. This rough structure will increase the porosity of the coating, thereby reducing the waterproofness and failing to maintain the anti-corrosion effect. Therefore, it is necessary to provide a water-based anti-corrosion coating and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention
[0005] In view of this, the present invention provides a water-based anti-corrosion coating and a preparation method thereof, so as to achieve the purpose of simultaneously improving the matte performance and waterproof performance of the coating and maintaining the anti-corrosion effect.
[0006] To achieve the above object, the present invention provides a method for preparing a water-based anticorrosive coating, comprising the following steps: S1, preparing modified carnauba wax microneedles: adding molten carnauba wax to a glass fiber dispersion, stirring evenly to obtain a mixed solution; pouring the mixed solution into a mold, cooling and solidifying, and drying to obtain modified carnauba wax microneedles; S2. Take water-based acrylic resin and water-based epoxy resin, add solvent and stir at low speed, add wetting agent and defoaming agent and stir at high speed; add modified TiO2 nanoparticles, siloxane acrylate, modified SiO2 nanoparticles and modified carnauba wax microneedles, mix and disperse evenly to obtain a water-based anti-corrosion coating.
[0007] The present invention uses glass fiber to modify carnauba wax to achieve complementary performance and obtain modified carnauba wax. First, the long-chain fatty acids and alcohol molecules of carnauba wax itself are hydrophobic, so that water cannot diffuse on the wax surface, forming water droplets with high contact angles, which are waterproof and improve the anti-corrosion effect; secondly, glass fiber and carnauba wax are used to form a composite structure, which enhances the toughness of carnauba wax and facilitates the preparation of microneedle structure; finally, the high tensile strength and elastic modulus of glass fiber can improve the deformation resistance of microneedles under bending and compression, and maintain the structural stability of microneedles.
[0008] The present invention introduces modified carnaba wax microneedles in the coating. On the one hand, the microneedle structure reduces the contact area between the droplet and the coating surface by increasing the surface roughness of the coating, and increases the contact angle, thereby realizing the super-hydrophobicity of the coating surface. The super-hydrophobic surface makes it difficult for water droplets to spread on the coating surface, and only forms beaded droplets, which are easy to roll and detach from the coating surface, to achieve the effect of preventing water penetration, further improving the anticorrosion, and because the beaded water droplets roll from top to bottom along the surface under the action of gravity, the dust, dirt and other tiny particles on the coating surface can be taken away in this process, thereby achieving the effect of self-cleaning. On the other hand, the microneedle structure increases the scattering path of light, can effectively scatter light, reduce the direct reflection of light, thereby improving the matte effect of the coating, and at the same time, modified silicon dioxide nanoparticles and modified titanium dioxide nanoparticles are filled in the pores brought by the microneedle structure, avoiding the increase in porosity brought by the improvement of surface roughness. Therefore, the introduction of modified carnaba wax microneedles can solve the problem of increased porosity brought by surface roughness, realize the simultaneous improvement of the anticorrosive performance and matte effect of the coating, and have a self-cleaning effect.
[0009] Optionally, the glass fiber dispersion is obtained by shearing glass fibers and dispersing them in anhydrous ethanol, and the glass fiber content is 0.04-0.06 g / ml; the conditions for stirring the molten carnaba wax in the glass fiber dispersion are a temperature of 90-100° C., a stirring speed of 1000-1200 rpm, and a stirring time of 25-35 min.
[0010] The high temperature when the carnaba wax is stirred in the glass fiber dispersion can ensure that the carnaba wax remains in a molten state, which facilitates uniform stirring.
[0011] Optionally, the parameters of the mold are a height of 10-20 μm and a diameter of 5-15 μm; the cooling and curing conditions are a temperature of 10-15° C. and a time of 1.5-2.5 h; and the drying conditions are a temperature of 45-55° C. and a time of 11-13 h.
[0012] Optionally, the method further includes adding modified kaurene in step S2, wherein the weight proportion of the modified kaurene is 2 to 4 parts, and the preparation of the modified kaurene includes the following steps: mixing COF-5 and methyltrimethoxysilane to obtain solution A, heating to react, filtering, washing, and drying to obtain modified COF-5; dissolving kaurene in dichloromethane to obtain solution B, adding the modified COF-5, stirring, filtering, washing, and drying to obtain modified kaurene.
[0013] The porous structure of COF-5 used in the present invention can increase the surface roughness of the coating, and can enhance the ability of the coating to scatter light, thereby achieving a matte effect. The use of modified carnauba wax microneedles together can better enhance the matte effect of the coating. However, COF-5 has poor dispersibility in the coating and is prone to agglomeration, which will affect the overall waterproof performance and matte effect of the coating. Therefore, MTMS (methyltrimethoxysilane) is used to modify COF-5, and organic silane functional groups are introduced into its surface after modification, which effectively improves the dispersibility of COF-5 in the coating. And MTMS has excellent hydrophobic properties, which not only improves the dispersibility of the coating, but also further improves the waterproofness and corrosion resistance of the coating.
[0014] Kaurene has excellent hydrophobicity, and loading it into modified COF-5 can further optimize the waterproof performance of the coating. The hydroxyl (-OH) groups in the kaurene molecule have significant antioxidant activity. These hydroxyl groups can donate hydrogen atoms to free radicals, converting them into a more stable non-free radical state, thereby neutralizing the free radicals and improving the antioxidant capacity of the coating. The conjugated double bonds in the kaurene molecule can stabilize the free radicals and disperse the energy of the free radicals through the conjugation effect, reducing their activity, inhibiting free radical reactions, and enhancing the antioxidant capacity of the coating. Moreover, the kaurene molecules and the Fe ions that catalyze the generation of free radicals 2+ , Cu 2+ Chelating reduces their ability to catalyze the generation of free radicals, thereby exerting an antioxidant effect. Through these effects, kaurene strengthens the antioxidant capacity of the coating and improves the durability of the coating. Kaurene molecules can be inserted into the bacterial cell membrane, changing the structure and permeability of the cell membrane, destroying the integrity of the cell membrane, causing the leakage of internal substances of the bacteria, leading to the loss of electrolytes and small molecules in the bacteria, and kaurene molecules can also inhibit the formation of cell membranes, thereby inhibiting bacterial growth, effectively improving the antibacterial properties of the coating and enhancing its antiseptic properties.
[0015] The present invention uses modified COF-5 to load kaurene, and the pore structure and large specific surface area of COF-5 can make the antioxidant and antibacterial properties of kaurene better play, and ensure that kaurene can stably play a role. The hydrophobicity of kaurene further strengthens the hydrophobicity of COF-5, thereby improving the waterproof performance of coating. Modified COF-5 can make kaurene uniformly dispersed in coating, make its antibacterial and antioxidant ability, can effectively play a role, improve the antibacterial and antioxidant ability of coating, make coating can be more durable and weather-resistant. In addition, COF-5 and kaurene are both environmentally friendly materials, do not contain harmful heavy metals and volatile organic compounds, and improve the environmental protection of coating.
[0016] Optionally, the mixing and stirring conditions of COF-5 and methyltrimethoxysilane are as follows: a stirring speed of 700-800 rpm, a stirring time of 1-1.5 h, and a content of COF-5 in the A solution of 0.04-0.06 g / ml; The heating is performed at a temperature of 55-60° C. for 4-6 hours; the conditions for dissolving kaurene in dichloromethane are a speed of 1000-1200 rpm and stirring for 30-40 minutes; the content of kaurene in the B solution is 0.02-0.04 g / ml; and the stirring conditions after adding the modified COF-5 are a speed of 600-800 rpm for 6-8 hours.
[0017] Optionally, the modified TiO2 nanoparticles are prepared by mixing TiO2 nanoparticles with anhydrous ethanol, adding methyltrimethoxysilane and mixing evenly, and filtering and drying to obtain the modified TiO2 nanoparticles; The preparation of the modified SiO2 nanoparticles is as follows: SiO2 nanoparticles are mixed with anhydrous ethanol, and ammonia water and ethyl stearate are added. After the mixture is evenly mixed, the solvent is evaporated to obtain the modified SiO2 nanoparticles.
[0018] The present invention reduces the surface energy of nanoparticles by using MTMS to modify TiO2 nanoparticles and ethyl stearate to modify SiO2 nanoparticles, improves the dispersibility of nanoparticles, and the modifier is compatible with the matrix material, improves the compatibility of nanoparticles, and avoids stress concentration caused by agglomeration. When the MTMS molecule reacts, the methoxy group in the molecule will undergo a hydrolysis reaction to generate silanol, and then the silanol molecule will undergo a hydrogen bond reaction and condensation with the hydroxyl group on the surface of the inorganic powder particle, thereby forming a -SiO-X covalent bond (X represents the surface of the inorganic powder particle). At the same time, the silanol molecules can also associate and polymerize with each other to form a covering material with a mesh structure, which is attached to the outer surface of the powder particle to improve the mechanical strength of the coating. In addition, both modifiers are hydrophobic, which further improves the waterproof performance of the coating and correspondingly improves the anti-corrosion performance. In addition, modified TiO2 nanoparticles and modified SiO2 nanoparticles can improve the surface roughness of the coating, so that the coating can have a good matte effect. They can also improve the wear resistance and weather resistance of the coating and extend the service life of the coating.
[0019] Optionally, the TiO2 content after the TiO2 nanoparticles are mixed with anhydrous ethanol is 0.1-0.15 g / ml, and the mass percentage of the methyltrimethoxysilane in the mixture of the TiO2 nanoparticles and anhydrous ethanol is 2-3 wt %; After the SiO2 nanoparticles are mixed with anhydrous ethanol, the SiO2 content is 0.1-0.15g / ml, the mass percentage of the ammonia water in the mixture of the SiO2 nanoparticles and anhydrous ethanol is 1-2wt%, and the mass percentage of the ethyl stearate in the mixture of the SiO2 nanoparticles and anhydrous ethanol is 4-6wt%.
[0020] Optionally, the low-speed stirring condition is a speed of 400-600 rpm and a time of 1-2 h; the high-speed stirring condition is 800-100 rpm and a time of 20-30 min.
[0021] Optionally, ultrasonic dispersion is performed after adding modified TiO2 nanoparticles and modified kaurene, and stirring is performed after adding silicone alkyl acrylate, modified SiO2 nanoparticles and modified carnauba wax microneedles.
[0022] The present invention uses different dispersing methods for different components to ensure that the components of the coating are evenly dispersed.
[0023] In order to achieve the above-mentioned purpose, the present invention also provides a water-based anti-corrosion coating prepared by a preparation method of the water-based anti-corrosion coating, comprising the following raw materials in parts by weight: 90-100 parts of water-based acrylic resin, 25-35 parts of water-based epoxy resin, 8-12 parts of xylene, 4-6 parts of butanone, 0.5-1 part of wetting agent, 0.5-1 part of defoaming agent, 4-6 parts of silicone acrylate, 8-12 parts of modified SiO2 nanoparticles, 3-7 parts of modified TiO2 nanoparticles, and 15-17 parts of modified carnauba wax microneedles.
[0024] The above technical solution of the present invention includes at least the following beneficial effects: The present invention adopts a modified additive in combination with modified TiO2 nanoparticles and modified SiO2 nanoparticles. On the one hand, modified carnauba wax microneedles are prepared by introducing glass fibers, and the structure of the modified carnauba wax microneedles is utilized to increase the surface roughness of the coating, thereby improving the diffuse scattering of light and enhancing the matte effect of the coating. The modified TiO2 nanoparticles and modified SiO2 nanoparticles are filled in the gaps caused by the microneedle structure, thereby avoiding the increase of pores caused by the surface roughness and further improving the matte effect. On the other hand, the microneedle structure also reduces the contact area between the droplet and the coating surface by increasing the surface roughness, increases the contact angle, and thus achieves super-hydrophobicity. The super-hydrophobic surface makes it easy for water droplets to roll and detach from the coating surface, preventing moisture penetration, further improving the waterproofness, and ensuring the overall anti-corrosion effect. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0026] Example 1 Preparation of modified TiO2 nanoparticles: Disperse 10g TiO2 nanoparticles in 100ml anhydrous ethanol, add 2wt% of the above mixture as silane coupling agent MTMS, stir for 2h, ultrasonically disperse for 60min, filter and dry for later use.
[0027] Preparation of modified SiO2 nanoparticles: Take 20g SiO2 nanoparticles, disperse them in 200ml anhydrous ethanol, stir evenly, add 1wt% ammonia water and 5wt% ethyl stearate, react for 4 hours under stirring conditions, evaporate the solvent and dry for later use.
[0028] Preparation of modified carnauba wax: Take 10g of glass fiber, shear it with a high-speed shearing machine, disperse it in 200ml of anhydrous ethanol, and ultrasonically disperse it for 30min to ensure that the glass fiber is evenly dispersed to obtain a glass fiber dispersion. Take 90g of carnauba wax, heat it to 100℃ to make it completely melted, slowly add the glass fiber dispersion, heat it to 90℃, start stirring, stir at 1000rpm for 30min to ensure that the glass fiber is evenly dispersed in the carnauba wax, and slowly pour the molten glass fiber modified carnauba wax into a mold with a height of 20 microns and a diameter of 15 microns to ensure that all mold pores are evenly filled, and cool it at 15℃ for 2h until it solidifies. Demolding, put the obtained microneedle sample into a vacuum drying oven, and dry it at 50℃ for 12h to obtain a modified carnauba wax microneedle. The modified carnauba wax microneedle is in a powder state after drying.
[0029] Mix 100 parts of water-based acrylic resin and 30 parts of water-based epoxy resin, add 10 parts of xylene and 5 parts of butanone as solvents, stir at 500 rpm for 1.5 hours, add 1 part of wetting agent BYK-348 and 1 part of defoaming agent BYK-141 after mixing evenly, and stir at 800 rpm for 30 minutes; add 5 parts of modified TiO2 nanoparticles, use ultrasonic dispersion for 60 minutes to ensure uniform distribution of particles; add 5 parts of siloxane acrylate, stir at 800 rpm for 30 minutes; add 10 parts of modified SiO2 nanoparticles, stir at 1000 rpm for 2 hours; add 15 parts of modified carnauba wax microneedles, stir at 800 rpm for 30 minutes to obtain a water-based anti-corrosion coating.
[0030] Example 2 Preparation of modified TiO2 nanoparticles: Disperse 12g TiO2 nanoparticles in 100ml anhydrous ethanol, add 3wt% of the above mixture as silane coupling agent MTMS, stir for 2h, ultrasonically disperse for 60min, filter and dry for later use.
[0031] Preparation of modified SiO2 nanoparticles: Take 26g SiO2 nanoparticles, disperse them in 200ml anhydrous ethanol, stir evenly, add 2wt% ammonia water and 4wt% ethyl stearate, react for 4 hours under stirring conditions, evaporate the solvent and dry for use.
[0032] Preparation of modified carnauba wax: Take 8g of glass fiber, shear it with a high-speed shearing machine, disperse it in 200ml of anhydrous ethanol, and ultrasonically disperse it for 30min to ensure that the glass fiber is evenly dispersed to obtain a glass fiber dispersion. Take 90g of carnauba wax, heat it to 90°C to make it completely melted, slowly add the glass fiber dispersion, heat it to 100°C, start stirring, stir at 1100rpm for 25min, ensure that the glass fiber is evenly dispersed in the carnauba wax, and slowly pour the molten glass fiber modified carnauba wax into a mold with a height of 10 microns and a diameter of 5 microns to ensure that all mold pores are evenly filled, and cool it at 12°C for 2.5h until it solidifies. Demolding, put the obtained microneedle sample into a vacuum drying oven, and dry it at 55°C for 11h to obtain a modified carnauba wax microneedle. The modified carnauba wax microneedle is in a powder state after drying.
[0033] Preparation of modified kaurene: Add 4g of dried COF-5 to 100ml of MTMS (methyltrimethoxysilane) solution, stir at 800rpm for 60min at room temperature to evenly disperse MTMS in the solution. Then heat the solution to 60℃ and react for 4 hours to allow the methoxy groups of MTMS to further condense with the hydroxyl groups on the surface of COF-5 to form a stable Si-O-Si bond. After the reaction, filter and wash the product, and dry it in a vacuum drying oven at 70℃ for 12h to obtain modified COF-5. Take 2g of kaurene and add it to 100ml of dichloromethane, stir at 1200rpm for 30min to ensure that it is dissolved in the solution. Add modified COF-5 to the solution, stir at 600rpm for 8h at room temperature to completely adsorb kaurene on the modified COF-5, filter and wash the product, and dry it at room temperature for 12h to obtain modified COF-5 loaded with kaurene.
[0034] Mix 90 parts of water-based acrylic resin and 35 parts of water-based epoxy resin, add 12 parts of xylene and 4 parts of butanone as solvents, stir at 400 rpm for 2 hours, add 0.5 parts of wetting agent BYK-348 and 0.8 parts of defoaming agent BYK-141 after mixing evenly, and stir at 900 rpm for 25 minutes; add 3 parts of modified TiO2 nanoparticles, use ultrasonic dispersion for 60 minutes to ensure uniform distribution of particles; add 6 parts of siloxane acrylate, stir at 800 rpm for 30 minutes; add 12 parts of modified SiO2 nanoparticles, stir at 1000 rpm for 2 hours; add 15 parts of modified carnauba wax microneedles, stir at 800 rpm for 30 minutes, and finally add 2 parts of modified COF-5 loaded kaurene, ultrasonically disperse for 30 minutes to ensure uniform dispersion, and obtain a water-based anti-corrosion coating.
[0035] Example 3 Preparation of modified TiO2 nanoparticles: Disperse 15g TiO2 nanoparticles in 100ml anhydrous ethanol, add 2.5wt% of the above mixture as silane coupling agent MTMS, stir for 2h, ultrasonically disperse for 60min, filter and dry for later use.
[0036] Preparation of modified SiO2 nanoparticles: Take 30g SiO2 nanoparticles, disperse them in 200ml anhydrous ethanol, stir evenly, add 1.5wt% ammonia water and 6wt% ethyl stearate, react for 4 hours under stirring conditions, evaporate the solvent and dry for use.
[0037] Preparation of modified carnauba wax: Take 12g of glass fiber, shear it with a high-speed shearing machine, disperse it in 200ml of anhydrous ethanol, and ultrasonically disperse it for 35min to ensure that the glass fiber is evenly dispersed to obtain a glass fiber dispersion. Take 90g of carnauba wax, heat it to 95°C to make it completely melted, slowly add the glass fiber dispersion, heat it to 95°C, start stirring, stir at 1200rpm for 35min, ensure that the glass fiber is evenly dispersed in the carnauba wax, slowly pour the molten glass fiber modified carnauba wax into a mold with a height of 15 microns and a diameter of 10 microns, ensure that all mold pores are evenly filled, and cool at 10°C for 1.5h until solidified. Demolding, put the obtained microneedle sample into a vacuum drying oven, dry it at 45°C for 13h, and obtain a modified carnauba wax microneedle. The modified carnauba wax microneedle is in a powder state after drying.
[0038] Preparation of modified kaurene: Add 6g of dried COF-5 to 100ml of MTMS (methyltrimethoxysilane) solution and stir at 700rpm for 1.5h at room temperature to evenly disperse MTMS in the solution. Then heat the solution to 55℃ and react for 6 hours to allow the methoxy groups of MTMS to further condense with the hydroxyl groups on the surface of COF-5 to form a stable Si-O-Si bond. After the reaction, filter and wash the product, and dry it in a vacuum drying oven at 70℃ for 12h to obtain modified COF-5. Take 4g of kaurene and add it to 100ml of dichloromethane, stir at 1000rpm for 40min to ensure that it is dissolved in the solution. Add modified COF-5 to the solution, stir at 800rpm for 6h at room temperature to completely adsorb kaurene on the modified COF-5, filter and wash the product, and dry it at room temperature for 12h to obtain modified COF-5 loaded with kaurene.
[0039] Mix 95 parts of water-based acrylic resin and 25 parts of water-based epoxy resin, add 8 parts of xylene and 6 parts of butanone as solvents, stir at 600 rpm for 1 hour, add 0.8 parts of wetting agent BYK-348 and 0.5 parts of defoaming agent BYK-141 after mixing evenly, and stir at 1000 rpm for 20 minutes; add 7 parts of modified TiO2 nanoparticles, use ultrasonic dispersion for 60 minutes to ensure uniform distribution of particles; add 4 parts of siloxane acrylate, stir at 800 rpm for 30 minutes; add 8 parts of modified SiO2 nanoparticles, stir at 1000 rpm for 2 hours; add 16 parts of modified carnauba wax microneedles, stir at 800 rpm for 30 minutes, and finally add 4 parts of modified COF-5 loaded kaurene, ultrasonically disperse for 30 minutes to ensure uniform dispersion, and obtain a water-based anti-corrosion coating.
[0040] Example 4 Compared with Example 1, the only difference is that the mold parameters of the modified carnabella wax microneedle are 12 microns in height and 7 microns in diameter, and the other raw materials and steps are consistent with Example 2.
[0041] Example 5 Compared with Example 1, the only difference is that the weight proportions of the components of the water-based anti-corrosion coating are 95 parts of water-based acrylic resin, 35 parts of water-based epoxy resin, 12 parts of xylene, 4 parts of butanone, 0.5 parts of wetting agent, 0.5 parts of defoaming agent, 4 parts of silicone acrylate, 12 parts of modified SiO2 nanoparticles, 7 parts of modified TiO2 nanoparticles and 17 parts of modified carnauba wax microneedles, and the remaining steps are consistent with Example 1.
[0042] Example 6 Compared with Example 2, the only difference is that the components of the water-based anti-corrosion coating are 100 parts by weight of water-based acrylic resin, 30 parts of water-based epoxy resin, 9 parts of xylene, 7 parts of butanone, 0.9 parts of wetting agent, 0.6 parts of defoaming agent, 5 parts of silicone acrylate, 10 parts of modified SiO2 nanoparticles, 5 parts of modified TiO2 nanoparticles, 15 parts of modified carnauba wax microneedles and 3 parts of modified kaurene, and the remaining steps are consistent with Example 2.
[0043] Comparative Example 1 Compared with Example 1, the only difference is that modified carnabella wax microneedles are not used, and the other raw materials and steps are consistent with Example 1.
[0044] Comparative Example 2 Compared with Example 1, the only difference is that modified TiO2 nanoparticles and modified SiO2 nanoparticles are not used, and the other raw materials and steps are consistent with Example 1.
[0045] Comparative Example 3 Compared with Example 2, the only difference is that modified carnauba wax microneedles, modified TiO2 nanoparticles and modified SiO2 nanoparticles are not used, and the remaining raw materials and steps are consistent with Example 2.
[0046] Comparative Example 4 Compared with Example 2, the only difference is that modified TiO2 nanoparticles and modified SiO2 nanoparticles are not used, and the remaining raw materials and steps are consistent with Example 2.
[0047] The basic performance tests were performed on the coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 4. The test results are shown in Table 1.
[0048] The hardness test method refers to the national standard GB / T6739-2022 "Determination of paint film hardness by pencil method for paints and varnishes". The hardness is assessed as follows: 9B, 8B, 7B, 6B, 5B, 4B, 3B, 2B, B, HB, F, H, 2H, 3H, 4H, 5H, 6H, 7H, 8H, 9H, and the hardness increases in sequence.
[0049] The adhesion test method refers to the national standard GB / T9286-2021 "Scratch Test for Paints and Varnishes", and the adhesion is assessed at levels 0 to 5, with the adhesion decreasing in sequence.
[0050] The aging resistance test method refers to the national standard GB / T1865-2009 "Artificial weathering and artificial radiation exposure of paints and varnishes to filtered xenon arc radiation", aging resistance assessment: whether it is chalking.
[0051] Table 1 Basic performance test results of coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 4
[0052] It can be seen from Table 1 that the coatings prepared in Examples 1 to 6 of the present invention are more excellent in hardness, adhesion and aging resistance than the coatings prepared in Comparative Examples 1 to 4.
[0053] From Table 1 combined with Example 2 and Comparative Example 4, it can be seen that modified TiO2 nanoparticles and modified SiO2 nanoparticles can improve the adhesion of the coating; from Table 1 combined with Comparative Example 2 and Comparative Example 4, it can be seen that modified kaurene is beneficial to improving the aging resistance of the coating.
[0054] The coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested for their waterproof and gloss properties. The test results are shown in Table 2.
[0055] The waterproof test method refers to the impermeability test method of the national standard GB / T16777-2008 "Test method for building waterproof coatings". The waterproof test assessment is: no water permeability within the specified time.
[0056] The gloss test method refers to the test method under 85° geometric conditions in the national standard GB / T9754-2007 "Determination of 20°, 60° and 85° specular gloss of paints and varnishes without metallic pigments". The smaller the gloss, the better the matte effect.
[0057] Table 2 Test results of waterproof and gloss properties of coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 4
[0058] It can be seen from Table 2 that the coatings prepared in Examples 1 to 6 of the present invention have stronger water resistance and lower glossiness than the coatings prepared in Comparative Examples 1 to 4, that is, better water resistance and matte effects.
[0059] It can be seen from Table 2 in combination with Example 1 and Comparative Examples 1-2 that the use of modified carnaba wax together with modified TiO2 nanoparticles and modified SiO2 nanoparticles improves the waterproofness and matte effect of the coating.
[0060] The coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested for antibacterial properties and self-cleaning effects. The test results are shown in Table 3.
[0061] The antibacterial test method refers to the national standard GB / T21866-2008 "Antibacterial property determination method and antibacterial effect of antibacterial coatings (paint films)", and the antibacterial evaluation is: Level I and Level II (Level I antibacterial property is higher than Level II).
[0062] The self-cleaning effect test method refers to the outdoor rain stain experiment in the national standard GB / T31815-2015 "Self-cleaning coatings for building exterior surfaces", and the self-cleaning effect is evaluated as follows: A, no rain stains; B, slight rain stains; C, obvious rain stains; D, severe rain stains.
[0063] Table 3 Antibacterial and self-cleaning performance test results of coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 4
[0064] It can be seen from Table 3 that, compared with the coatings prepared in Comparative Examples 1 to 4, the coatings prepared in Examples 1 to 6 of the present invention have better antibacterial properties and self-cleaning effects.
[0065] Combining Table 2 and Table 3, it can be seen that the coatings prepared in Examples 1 to 6 of the present invention have more excellent antibacterial and waterproof properties, and achieve an excellent anti-corrosion effect as a whole.
[0066] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a water-based anticorrosive coating, characterized in that: The following steps are involved: S1. Preparing modified carnauba wax microneedles: adding molten carnauba wax to a glass fiber dispersion, stirring evenly to obtain a mixed solution; pouring the mixed solution into a mold, cooling and solidifying, and drying to obtain modified carnauba wax microneedles; S2. Take water-based acrylic resin and water-based epoxy resin, add solvent and stir at low speed, add wetting agent and defoaming agent and stir at high speed; add modified TiO2 nanoparticles, siloxane acrylate, modified SiO2 nanoparticles and modified carnauba wax microneedles, mix and disperse evenly to obtain a water-based anti-corrosion coating.
2. The method for preparing the water-based anticorrosive coating according to claim 1, characterized in that: The glass fiber dispersion is obtained by shearing glass fibers and adding them into anhydrous ethanol for dispersion, and the content of glass fibers is 0.04-0.06 g / ml; the conditions for stirring molten carnaba wax in the glass fiber dispersion are temperature 90-100° C., stirring speed 1000-1200 rpm, and stirring time 25-35 min.
3. The method for preparing the water-based anticorrosive coating according to claim 1, characterized in that: The parameters of the mold are a height of 10-20 μm and a diameter of 5-15 μm; the cooling and curing conditions are a temperature of 10-15° C. and a time of 1.5-2.5 h; and the drying conditions are a temperature of 45-55° C. and a time of 11-13 h.
4. The method for preparing a water-based anticorrosive coating according to claim 1, characterized in that: The method further includes adding modified kaurene in step S2, wherein the weight proportion of the modified kaurene is 2 to 4 parts, and the preparation of the modified kaurene includes the following steps: mixing COF-5 and methyltrimethoxysilane to obtain solution A, heating to react, filtering, washing, and drying to obtain modified COF-5; dissolving kaurene in dichloromethane to obtain solution B, adding the modified COF-5, stirring, filtering, washing, and drying to obtain modified kaurene.
5. The method for preparing the water-based anticorrosive coating according to claim 4, characterized in that: The mixing conditions of COF-5 and methyltrimethoxysilane are as follows: a stirring speed of 700-800 rpm, a stirring time of 1-1.5 h, and a content of COF-5 in the solution A of 0.04-0.06 g / ml; The heating is performed at a temperature of 55-60° C. for 4-6 hours; the conditions for dissolving kaurene in dichloromethane are a speed of 1000-1200 rpm and stirring for 30-40 minutes; the content of kaurene in the B solution is 0.02-0.04 g / ml; and the stirring conditions after adding the modified COF-5 are a speed of 600-800 rpm for 6-8 hours.
6. The method for preparing a water-based anticorrosive coating according to claim 1, characterized in that: Preparation of the modified TiO2 nanoparticles: Mix TiO2 nanoparticles with anhydrous ethanol, add methyltrimethoxysilane and mix evenly, filter and dry to obtain the modified TiO2 nanoparticles; The preparation of the modified SiO2 nanoparticles is as follows: SiO2 nanoparticles are mixed with anhydrous ethanol, and ammonia water and ethyl stearate are added. After the mixture is evenly mixed, the solvent is evaporated to obtain the modified SiO2 nanoparticles.
7. The method for preparing the water-based anticorrosive coating according to claim 6, characterized in that: After the TiO2 nanoparticles are mixed with anhydrous ethanol, the content of TiO2 is 0.1-0.15 g / ml, and the mass percentage of the methyltrimethoxysilane in the mixture of the TiO2 nanoparticles and anhydrous ethanol is 2-3 wt %; After the SiO2 nanoparticles are mixed with anhydrous ethanol, the SiO2 content is 0.1-0.15g / ml, the mass percentage of the ammonia water in the mixture of the SiO2 nanoparticles and anhydrous ethanol is 1-2wt%, and the mass percentage of the ethyl stearate in the mixture of the SiO2 nanoparticles and anhydrous ethanol is 4-6wt%.
8. The method for preparing a water-based anticorrosive coating according to claim 1, characterized in that: The low-speed stirring condition is 400-600 rpm for 1-2 h; the high-speed stirring condition is 800-1000 rpm for 20-30 min.
9. The method for preparing a water-based anticorrosive coating according to claim 4, characterized in that: After adding the modified TiO2 nanoparticles and the modified kaurene, ultrasonic dispersion was performed respectively, and after adding the silicone alkyl acrylate, the modified SiO2 nanoparticles and the modified carnauba wax microneedles, stirring was performed respectively.
10. A water-based anti-corrosion coating prepared by the method for preparing a water-based anti-corrosion coating according to any one of claims 1 to 9, characterized in that: The invention comprises the following raw materials in parts by weight: 90-100 parts of water-based acrylic resin, 25-35 parts of water-based epoxy resin, 8-12 parts of xylene, 4-6 parts of butanone, 0.5-1 part of wetting agent, 0.5-1 part of defoaming agent, 4-6 parts of silicone acrylate, 8-12 parts of modified SiO2 nanoparticles, 3-7 parts of modified TiO2 nanoparticles and 15-17 parts of modified carnauba wax microneedles.
Citation Information
Patent Citations
Matte stain-resistant waterproof coating material for exterior walls, preparation method and use method thereof
CN113969088A
Anti-corrosion super-hydrophobic heat reflecting paint and preparation method thereof
CN105925073A
Preparation method of Tenebrio molitor culture wooden case inner wall paint
CN105936795A
Modified waterborne acrylic resin paint preparation method
CN106189640A
Anticorrosive coating and preparation method thereof
CN106519765A
Cited By
Modified siloxane defoaming agent and preparation method thereof
CN120285620A